An analysis of the aims of Turkish Amateur Sports Club Confederation board members who entered management positions - Coban, Bilal (Academic Journals, 2010)
This study analyzed the objectives of the Amateur Sports Clubs Confederation (ASCC) board members who took managerial positions. Volunteer sport unions in Turkey are oriented towards advancement in Sport Management, contribution to the process of change and development and joining the management in the field of sports. Among these unions, ASCC has an important role. A survey model was used to determine the views of ASCC members of the board. Data was collected through questionnaires and a total of 459 questionnaires were evaluated. Population of the study consisted of ASCC members of the board in 74 different provinces. The study sampling consisted of ASCC members of the board in 62 provinces. Statistical analysis indicated that KMO value of the questionnaire was 0.85, Barlette test was 9416.078 and Cronbach's Alpha reliability coefficient was 0.89. As for the distribution of the views of ASCC members of the board according to types of positions, there was a parallelism between the views of secretaries, managers and vice-managers. However, there was a difference between the views of secretaries and members. This difference can be interpreted by the fact that members of the board holding positions requiring closer contact with the manager, or the ones undertaking a more active participation, can realize their expectations in joining ASCC management. It can be suggested that full participation of board members in the decision-making process will contribute to the formation of a democratic society and will have a positive effect on democratic developments in sport.
Keywords: TASCC; ASCC; sport; joining management; non-governmental organization